Remediation of heavy metal(loid) contaminated soil through green nanotechnology - Mathur, Shivangi; Singh, Deeksha; Ranjan, Rajiv (Frontiers in Sustainable Food Systems, 2022)
Modern industrialization is progressively degrading soil quality due to heavy metal contamination. Heavy metal (HM) contamination of agricultural soil has gained considerable attention due to its rapidly increasing levels. Nanoparticles (NPs) have unique physicochemical properties that make them effective stress relievers. Material science has recently been emphasizing "green" synthesis as a reliable, environmentally friendly, and sustainable method of synthesizing different kinds of materials, such as alloys, metal oxides, hybrids, and bioinspired materials. Therefore, green synthesis can be viewed as an effective tool to reduce the detrimental effects of the traditional nanoparticle synthesis methods commonly used in laboratories and industries. The review briefly describes the biosynthesis of NPs, the use of nanobiotechnology to remediate heavy metal-contaminated soil, the effect that NPs have on growth and development of plants, the behavior of NPs within plants when exposed to pollutants and the mechanisms used to alleviate HM stress. In addition, a broad overview of the major types of nanomaterials used so far in bioremediation of toxic heavy materials, recent advances regarding HM stress and the possible mechanisms by which NPs and HM interact in the agricultural system are also discussed.